Building A Culture of Democracy in The Digital Space by Optimizing Students' Learning Attention Through Mentimeter - Karyadi Hidayat; Rohman Rohman; Nikki Tri Sakung (Jurnal Kewarganegaraan, 2026)
The low level of ethical communication in cyberspace is a major challenge to digital democracy, while Civics (PPKn) learning often faces the challenge of low student attention. This quantitative, quasi-experimental study with a Non-equivalent Control Group Design aims to analyze the effectiveness of the Mentimeter platform in optimizing Civics students' learning attention while simultaneously building a culture of digital democracy. The research sample consisted of 70 students divided into an experimental class (n=35) and a control class (n=35). Data were analyzed using the Independent Samples t-Test and N-Gain Score. The results showed that the experimental class experienced a statistically significant (p <0.05) increase in learning attention (N-Gain = 0.58) and a strengthening of digital democratic culture (N-Gain = 0.62) compared to the control class. Mentimeter's anonymity and real-time visualization features have proven effective in creating an inclusive and deliberative discourse space. Optimizing learning attention through interactive digital media is linearly correlated with the development of critical digital citizen character.